Qual reforma da educação profissional e para qual compreensão de estado? - Torres Ribeiro, Ricardo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Indicates the idea of reform of state in the government of Fernando Henrique Cardoso (FHC) with developments in the Brazilian professional education policy. Highlights up the performance of Bresser-Pereira as a major mentor of the idea of reforming state within neoliberal and conservative principles. Inquires up how element to a later deepening of research if the most contemporary educational policies during periods Lula and Dilma Rousseff represent a continuity (or discontinuity) with the government FHC.
Keywords: State; Professional Education; Public Policy